ANALISIS DAMPAK SANKSI EKONOMI BARAT TERHADAP STRATEGI RUSIA DALAM IMPOR TEKSTIL - Narendra, Pangestu Galih; Prinanda, Devita (Department of International Relations, Universitas Brawijaya, 2024)
War between Russia and Ukraine, which started from early February 2022 had already giving significant impact on Russian economy. Many of Russian economic dan industrial sectors had slowed down or halted due to economic sanctions from Western countries, who were allies for Ukraine and NATO. One of those sectors is Russian textile and garment industries. This journal has a purpose to explain how Western economic sanctions affect Russian decision making on export-import activity of textile and garment industries. By using economic sanctions theory and qualitative methods, and literature study to gather data about the effect of western economic sanction towards Russian textile industri and responds from Russia in handling its textile and garment industry. Keywords: Textile dan Garment Industry, Russo-Ukrainian War, Russian Economy, Western Economic Sanctions